The microbiome of pediatric patients with chronic rhinosinusitis. Issue 1 (22nd June 2020) - Stapleton, Amanda L.; Shaffer, Amber D.; Morris, Alison; Li, Kelvin; Fitch, Adam; Methé, Barbara A.
Abstract : Background: This study aimed to compare the microbiota of pediatric patients with chronic rhinosinusitis (CRS) who are undergoing adenoidectomy to treat their disease with that of healthy control patients. Methods: Patients undergoing adenoidectomy‐only for obstructive sleep apnea (n = 50) and CRS (n = 37) were recruited. Preoperative 22‐item Sino‐Nasal Outcome Test (SNOT‐22) or Sinus and Nasal Quality of Life Survey (SN‐5) were collected. Each patient had samples collected from their nasopharynx (adenoid bed) and nasal cavity (sinus) at the onset of surgery. 16S ribosomal ribonucleic acid (rRNA) gene sequencing was subsequently performed to obtain per sample taxonomic abundances. Statistical analyses included permutational multivariate analysis of variance (PERMANOVA), alpha (within sample) diversity measures, and changes in taxonomic abundance. Results: Moraxella was the most abundant organism. Nasopharyngeal swabs demonstrated higher alpha diversity compared to the nasal cavity. The diversity was not different based on CRS vs obstructive history. There was an increase in diversity with increasing age, and eczema contributed to a greater difference in diversity between the nasopharynx and nasal cavity. Diversity was not affected by adenoid size; however, use of nasal steroids, inhaled steroids, and antihistamines influenced diversity in both the nasopharynx and nasal cavity. Nasopharyngeal samples were higher in relative abundance for Fusobacterium, Prevotella, Porphyromonas, and Campylobacter compared to the nasal cavity. Conclusion: The nasopharynx and nasal cavity differed in both microbiota composition and diversity. In contrast, no significant difference in composition or diversity were found in CRS vs control patients. Ecological changes in the nasopharyngeal and sinus site may contribute to the etiology for adenoid hypertrophy in both healthy controls and CRS patients.